A Bibliometric Review of Creative Economy Entrepreneurship: Implications for Community Empowerment Strategies - Judijanto, Loso; Puspa, Leonora; Thalib, Najdah (Westscience Press, 2024)
This study presents a bibliometric review of creative economy entrepreneurship, focusing on its implications for community empowerment strategies. Using data from Google Scholar and Scopus, the analysis covers publications from 1997 to 2024. The VOSviewer software was used to conduct co-citation, keyword co-occurrence, and network mapping analyses to identify key research trends, influential authors, and emerging topics. Results show that